The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0959353516674493
|View full text |Cite
|
Sign up to set email alerts
|

Women’s constructions of heterosex and sexual embodiment after cancer

Abstract: The significant impact of cancer on women's sexual well-being has been acknowledged increasingly within research. However, the role of cultural discourse in shaping women's construction and embodied experience of sexuality has received less attention. In this study, we examined heterosexual women's constructions of sexual embodiment in the context of cancer. Sixteen women across a range of ages (20-71 years), cancer types and stages took part in in-depth semi-structured interviews. A thematic decomposition ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…This includes changes to the meaning of sex when natural conception is unlikely, feelings of pressure associated with efforts to conceive, and the need to have sex at a scheduled time, which can impact negatively on sexual desire, arousal and couple sexual enjoyment (Zhuoran et al, 2017). While all couples facing infertility may experience psychosexual changes, participants in this study described additional couple distress due to changes in sexual function associated with cancer treatment, as has previously been reported (Parton et al, 2017). Feelings of inadequacy associated with not being able to ‘provide’ a child within a couple relationship may also have an impact on psychosexual well‐being, as reported previously (Lehmann et al, 2018).…”
Section: Discussionsupporting
confidence: 66%
“…This includes changes to the meaning of sex when natural conception is unlikely, feelings of pressure associated with efforts to conceive, and the need to have sex at a scheduled time, which can impact negatively on sexual desire, arousal and couple sexual enjoyment (Zhuoran et al, 2017). While all couples facing infertility may experience psychosexual changes, participants in this study described additional couple distress due to changes in sexual function associated with cancer treatment, as has previously been reported (Parton et al, 2017). Feelings of inadequacy associated with not being able to ‘provide’ a child within a couple relationship may also have an impact on psychosexual well‐being, as reported previously (Lehmann et al, 2018).…”
Section: Discussionsupporting
confidence: 66%
“…According to the interpretations of the participants, mastectomy is initially accepted as a necessary operation that saves their life. However, physical changes create a sense of difference, due to the loss of health on the one hand and the loss of femininity on the other [15,16]. Analytically, it appeared that the sense of diversity is influenced by its values and norms modern society and from the way of behavior adopted by the partner, as well and the family and social environment.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that women who experience pain and physical discomfort during sex can construct themselves as being inadequate women as they are not able to comfortably participate in this social practice (Ussher et al, 2013). This is evident in research on chronic illnesses where women's bodies have changed due to their illness and treatment, such as pain and reduced sexual desire or sensation in genital areas (Parton et al, 2016(Parton et al, , 2017Ussher et al, 2013). Women report continuing to practice coitus even when they experience pain (Ayling & Ussher, 2007;McPhillips et al, 2001;Parton et al, 2017).…”
Section: Discourses Of Hetero-femininitymentioning
confidence: 99%
“…This is evident in research on chronic illnesses where women's bodies have changed due to their illness and treatment, such as pain and reduced sexual desire or sensation in genital areas (Parton et al, 2016(Parton et al, , 2017Ussher et al, 2013). Women report continuing to practice coitus even when they experience pain (Ayling & Ussher, 2007;McPhillips et al, 2001;Parton et al, 2017).…”
Section: Discourses Of Hetero-femininitymentioning
confidence: 99%
See 1 more Smart Citation